Common law in the conditions of self-government in Kyiv Rus - Єрєгян, Анаїда Робертівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
An attempt to study the process of interference of custom as original form of law and self-government in Kyiv Rus was undertaken in the article.